Կաչաղակաբերդ - Ս. Ա. Սարգսյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Изучение памятников ущелья реки Хачен дает возможность уточнить местонахождение крепости Качахакаберд—исторической области Арцаха. Сравнительный анализ письменных источников наводит на мысль, что крепость Хачен—это та же крепость Качахакаберд. Строители искусно использовали преимущества горного ландшафта и соорудили неприступную крепость. The study of the monuments situated in the valley of the River Khachen in the Artsakh province of historic Armenia makes it possible to identify the site of Fort Kachaghakaberd.A comparative analysis of written sources conclusively leads to the idea that the fort of Khachen is the same as Kachaghakaberd itself. The builders of the fort have skillfully made use of the high mountainous site and its advantages thus acquiring the possibility of founding such a unique fort that has left a remarkable imprint in the glorious history of the Armenian people.
Keywords: History; Auxiliary Sciences of History; CC Archaeology; D History; N Fine Arts; NA Architecture